Exploring the potential of social media platforms to foster cultural diversity and enhance intercultural comprehension among EFL university students - Mahmood, Hemn Mohammed Ali; Ghafar, Zanyar Nathir; Saeed, Hawraz Mahmood Hama; Hamarasheed, Aya Soran; Ali, Tolaz Mohammed (Yayasan Mitra Persada Nusantara, 2024)
This research aimed to investigate how social media platforms promote cultural diversity and improve intercultural understanding among their users. To accomplish these goals, the research used qualitative methods for gathering data, particularly by conducting in-depth interviews with a group of 12 students who are currently enrolled in the English department at Halabja University. The study findings indicate that social media platforms are widely recognized as essential tools that enable users to access and acquire knowledge about various cultures, and these platforms provide a space for users to engage with individuals from different backgrounds and gain exposure to new perspectives. In conclusion, identifying obstacles that hinder the integration of cultural diversity and suggesting specific solutions to overcome these issues provides valuable knowledge on using social media platforms to enhance cross-cultural communication and understanding. Additionally, the study aimed to identify barriers that impede the integration of cultural diversity and suggest appropriate solutions.